PEMANFAATAN PERANGKAT TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN - Raliyanti - (Madaris: Jurnal Guru Inovatif, 2022)
ABSTRACT This is a time when information and communication technology (ICT) is growing very rapidly. ICT has now touched almost every aspect of modern life that makes its own power for the genaration that lives in this century. Over time, the development of ICT is bringing people to a higher level of civilization with new problems to deal with. Previously, one of the problems was the digital divide, but over time and the development of market dynamics, information technology became cheaper and affordable for everyone. That's when the problem of how technology is started. This study discusses about how the utilization of information technology to students in Madrasah Aliyah Negeri (MAN) 4 Jakarta. This study is judged on the opinions and theories of several experts from various literatures. This study discusses the use of information and communication technology based on the use of information and communication technology tools in learning up to the assessment process. The results of this study indicate that the use of information and communication technology in Madarsah Aliyah Negeri (MAN) 4 is sufficient and effective use as a means of information complementary teaching materials to utilization for computer-based assessment. Keywords—hardware, technology, information, communication, education